Effect of Different Microstructures on Surface Residual Stress of Induction-Hardened Bearing Steel - Shao-Quan Lu; Liu-Ho Chiu (Metals, 2024)
JIS SUJ2 steel is most widely used in bearing steel. The advantages are good hardenability, excellent fatigue, wear resistance and comprehensive mechanical properties. The wear resistance and fatigue resistance of this steel are attracting more attention, and the residual stress state and its distribution on the surface of the heat affected zone are critical factors affecting the fatigue life and wear resistance of the parts. In this study, SUJ2 is used as a material by which to study the surface residual stress and retained austenite distribution of induction-hardened steel. Quenching and tempering treatments were used to obtain different microstructures and an induction method was used to re-quench the case region. After the heat treatment, the residual stress and retained austenite volume on the surface were analyzed by X-ray diffraction and analyses of the microstructure and the hardness were also conducted. The results show that the microstructure after heat treatment contains unsolved carbides, tempered martensite and retained austenite. In the induction-hardened area, the residual stress is all compressive, and the values are more than −750 MPa. In conclusion, the microstructures of the specimens before induction hardening have a significant impact on the effective case depth for the same output power condition and the surface residual stress changes from a tensile to a compressive state. In the induction-hardened area, the maximum of the residual compressive stress was increased as the austenitized temperature of quenching increased.